Cyber conflict : competing national perspectives - Ventre, Daniel (London : ISTE ; Hoboken, NJ : John Wiley & Sons, 2012)
Today, cyber security, cyber defense, information warfare and cyber warfare issues are among the most relevant topics both at the national and international level. All the major states of the world are facing cyber threats and trying to understand how cyberspace could be used to increase power. Through an empirical, conceptual and theoretical approach, Cyber Conflict has been written by researchers and experts in the fields of cyber security, cyber defense and information warfare. It aims to analyze the processes of information warfare and cyber warfare through historical, operational.
Canada's cyber security policy: a tortuous path toward a cyber security strategy / Hugo Loiseau and Lina Lemay -- Cuba: towards and active cyber-defense / Daniel Ventre -- French perspectives on cyber-conflict / Daniel Ventre -- Digital Sparta: information operations and cyber-warfare in Greece / Joseph Fitsanakis -- Moving toward and Italian cyber defense and security strategy / Stefania Ducci -- Cyberspace in Japan's new defense strategy / Daniel Ventre -- Singapore's encounter with information warfare: filtering electronic globalization and military enhancements / Alan Chong -- A Slovenian perspective on cyber warfare / Gorazd Praprotnik, Iztok Podbregar, Igor Bernik and Bojan Ticar -- A South African perspective on information warfare and cyber warfare / Brett Van Niekerk and Manoj Maharaj -- Conclusion / Daniel Ventre.
Includes bibliographical references and index.
Print version record.
Keywords: Cyberterrorism -- Prevention; Cyberspace -- Security measures; Computer networks -- Security measures; Information warfare; National security; Computer networks -- Security measures; Cyberspace -- Security measures; Cyberterrorism -- Prevention; Information warfare; National security; POLITICAL SCIENCE -- Political Freedom & Security -- Terrorism; Information warfare; Electronic books; Electronic books